LINGUOCULTURAL ASPECT OF PURELY COMPARATIVE EXPRESSIONS IN THE LINGUISTIC PICTURE OF THE WORLD (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Along with the reflection of the people's way of life through comparison, the reflection of the people's wisdom and the nation's psyche testifies to the infinite importance of this method of expression. Folk proverbs, formed on the basis of comparison, are a vivid proof of this. Through the comparison of folk proverbs, one can understand that our people are blessed, noble, hospitable, and wise, who know the value of things.